2004
DOI: 10.1038/nature02756
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale imaging of nanoengineered oxygen vacancy profiles in SrTiO3

Abstract: At the heart of modern oxide chemistry lies the recognition that beneficial (as well as deleterious) materials properties can be obtained by deliberate deviations of oxygen atom occupancy from the ideal stoichiometry. Conversely, the capability to control and confine oxygen vacancies will be important to realize the full potential of perovskite ferroelectric materials, varistors and field-effect devices. In transition metal oxides, oxygen vacancies are generally electron donors, and in strontium titanate (SrTi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
478
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(511 citation statements)
references
References 28 publications
31
478
2
Order By: Relevance
“…Particularly, clusters of oxygen vacancies can act as localizing sites for such itinerant electrons 25,26 and clustering of vacancies is a common feature in PLD grown STO thin films grown under low pressures. 27 In the case of samples containing 15% La, the low temperature resistivity is best described by ρ ∼ sinh 2 ( 1 T ), characteristic of small polaron conduction. Recently, Liang et al 28 suggested the possibility of small polaron conduction in 15% La doped STO films grown under similar conditions, corroborating our observation.…”
Section: B Optical Spectroscopymentioning
confidence: 99%
“…Particularly, clusters of oxygen vacancies can act as localizing sites for such itinerant electrons 25,26 and clustering of vacancies is a common feature in PLD grown STO thin films grown under low pressures. 27 In the case of samples containing 15% La, the low temperature resistivity is best described by ρ ∼ sinh 2 ( 1 T ), characteristic of small polaron conduction. Recently, Liang et al 28 suggested the possibility of small polaron conduction in 15% La doped STO films grown under similar conditions, corroborating our observation.…”
Section: B Optical Spectroscopymentioning
confidence: 99%
“…The vacancies either form along a network of extended defects 6 or assemble together to lower the system's energy 7,8 , probably producing large positively charged donor clusters. Another way to more controllably create such a cluster is to "draw" a disc of charge by the atomic force microscope (AFM) tip on the surface of LAO/STO structure with the subcritical thickness for LaAlO 3 (LAO) 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…10.3c. [27] and Nb 4+ /Nb 5+ [28] from previous studies are also plotted for comparison. Reprinted with permission from [22].…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%
“…Figure 10.4 shows the EELS spectra acquired around the Ti L (c) and O K edges (d). The reported EELS spectra of Ti 3+ /Ti 4+ [27] and Nb 4+ /Nb 5+ [28] are plotted for comparison. In the Ti L edge spectrum (c), t 2g and e. g. peak splitting is clearly observed for Ti L 3 , indicating that the dominant valence state of Ti is 4+.…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%